silencing suppressor P25 of Potato virus X interacts with Argonaute1 and mediates its degradation through the proteasome pathway - CHIU, MENG-HSUEN; CHEN, I-HSUAN; BAULCOMBE, DAVID C; TSAI, CHING-HSIU (Molecular plant pathology, 2010)
Previous evidence has indicated that the P25 protein encoded by Potato virus X (PVX) inhibits either the assembly or function of the effector complexes in the RNA silencing-based antiviral defence system (Bayne et al., Cell-to-cell movement of Potato Potexvirus X is dependent on suppression of RNA silencing. Plant J.44, 471-482). This finding prompted us to investigate the possibility that P25 targets the Argonaute (AGO) effector nuclease of RNA silencing. Co-immunoprecipitation and Western blot analysis indicated that there is a strong interaction between P25 and AGO1 of Arabidopsis when these proteins are transiently co-expressed in Nicotiana benthamiana. P25 also interacts with AGO1, AGO2, AGO3 and AGO4, but not with AGO5 and AGO9. As an effective suppressor, the amount of AGO1 accumulated in the presence of P25 was dramatically lower than that infiltrated with HcPro, but was restored when treated with a proteasome inhibitor MG132. These findings are consistent with the idea that RNA silencing is an antiviral defence mechanism and that the counter-defence role of P25 is through the degradation of AGO proteins via the proteasome pathway. Further support for this idea is provided by the observation that plants treated with MG132 are less susceptible to PVX and its relative Bamboo mosaic virus.